Hepatitis B Virus (HBV) Infection and Re-activation During Nucleos(t)ide Reverse Transcriptase Inhibitor–Sparing Antiretroviral Therapy in a High–HBV Endemicity Setting. (5th October 2018) - Abdullahi, Adam; Fopoussi, Olga Mafotsing; Torimiro, Judith; Atkins, Mark; Kouanfack, Charles; Geretti, Anna Maria
Abstract: Background: We monitored the evolution of markers of hepatitis B virus (HBV) infection in virologically suppressed HIV-positive patients switching to nucleoside reverse transcriptase inhibitor (NRTI)–sparing antiretroviral therapy within a randomized trial in Cameroon. Methods:   HBV surface antigen (HBsAg), HBV DNA, and antibodies against surface (anti-HBs), core (total anti-HBc), and e-antigen (anti-HBe) were measured retrospectively in samples collected at study entry and over 48 weeks after NRTI discontinuation. Results: Participants (n = 80, 75% females) had a plasma HIV-1 RNA <60 copies/mL, a median CD4 count of 466 cells/mm 3, and undetectable HBsAg and HBV DNA at study entry. After NRTI discontinuation, 3/20 (15.0%) anti-HBc-negative patients showed evidence indicative or suggestive of incident HBV infection (163 cases/1000 person-years); 6/60 (10.0%) anti-HBc-positive patients showed evidence indicative or suggestive of HBV reactivation (109 cases/1000 person-years). In one case of reactivation, anti-HBs increased from 14 to >1000 IU/L; sequencing showed HBV genotype A3 and 3 escape mutations in surface (Y100C, K122R, Y161FY). Alongside new-onset detection of HBsAg or HBV DNA, 1 patient experienced acute hepatitis and 6 patients experienced mild or marginal increases in serum transaminase levels. Conclusions: Evolving treatment strategies for sub-Saharan Africa must be accompanied by the formulation and implementation of policy to guide appropriate assessment and management of HBV status.